Intracranial venous thrombosis in a man taking clomiphene citrate - Zahid, M (BMJ Case Rep, 2016)
Clomiphene citrate is widely used by the female population for the management of a wide array of medical conditions especially those related to ovulation, but its use in male population remains controversial. Efficacy of clomiphene is not well established in male hypogonadism and infertility. Its side effects and complications are also poorly studied or reported. We present a case of a man with infertility issues for which he started receiving clomiphene citrate 3 weeks before presenting with progressive symptoms of headache, vomiting, transient blurred vision and diplopia, which eventually turned out to be the symptoms of intracranial venous thrombosis. After excluding the common causes of intracranial venous thrombosis and hypercoagulable state, clomiphene citrate seems the most likely culprit.